Long-distance electrical signals as a link between the local action of stressors and the systemic physiological responses in higher plants - Sukhov, Vladimir; Sukhova, Ekaterina; Vodeneev, Vladimir (Progress in biophysics and molecular biology, 2019)
Our review is devoted to the analysis of the role of long-distance electrical signals in the development of the fast systemic physiological responses in higher plants. The characteristics and mechanisms of basic electrical signals (variation potential, action potential and system potential) are analyzed, and a potential schema of the generation and propagation of the system potential is proposed. The review summarizes the physiological changes induced by the variation potential, action potential and system potential in higher plants, including changes in gene expressions, the production of phytohormones, photosynthesis, phloem mass-flow, respiration, ATP content, transpiration and plant growth. Potential mechanisms of the changes are analyzed. Finally, a hypothetical schema, which describes a hierarchy of the variation potential, action potential and system potential, in the development of the fast systemic non-specific adaptation of plants to stressors, is proposed.